Infection with SARS-CoV-2 causes flares in patients with juvenile idiopathic arthritis in remission or inactive disease on medication - Boris Hügle (BMC, 2021)
Abstract Background Flares of juvenile idiopathic arthritis (JIA) have been described in the context of various infections. Flares of rheumatic diseases in adults have been described following infection with SARS-CoV-2 in several cohorts. So far, the effect of infection with SARS-CoV-2 on the course of JIA is unknown. Methods The database of the German Center for Pediatric and Adolescent Rheumatology was searched for patients with confirmed infection with SARS-CoV-2 and subsequent disease flare, admitted from July 2020 until June 2021. cJADAS-27, ESR and C-reactive protein, as well as uveitis activity, medication at the time of flare and treatment of flare was extracted. Patient cases were described individually. Results Out of 988 patients admitted, five patients with remission off medication (n = 2) or inactive disease on medication (n = 3) were identified, with flare symptoms up to four weeks after infection with SARS-CoV-2. Conclusions Flares can occur after infection with SARS-CoV-2 in patients with JIA in remission or inactive disease on medication. Treating physicians need to be aware of this fact, especially when counseling patients with rheumatic diseases about the respective dangers of COVID-19 and vaccination against SARS-CoV-2.